Características del estado de salud mental de jóvenes en condiciones vulnerables (2013)
ABSTRACT: To describe mental health profile of school teenagers from La Cruz neighborhood; a deprived sector of Medellin and to establish the possible relation with the level of risks of other psychosocial variables.Methods: a descriptive-quantitative and cross-sectional research conducted in 2011 by using a self-applied instrument in 100 young people between 11 and 19 years of age. Results: meaningful stressful psychosocial variables were identified for pharmacodependency and for positive correlation among the family functioning level, the depression level and the suicide risk. Conclusions: the young people are affected by critical psychosocial situations that generate communication difficulties for them, in search of support and with the feeling of happiness that life can offer them. It is necessary to implement effective public policies in terms of integrating education, which assist these young people in exploring other living options and promote health and justice that will multiply their opportunities.